Polarographic Study of Dicarboxylic-Acid-dependent Export of Reducing Equivalents from Illuminated Chloroplasts - Anderson, John W. (1979)
Isolated pea chloroplasts, prepared by differential centrifugation, catalyzed O(2) evolution in the light in the presence of 0.03 to 3 millimolar malate, 0.12 to 1.2 millimolar NAD, 4 millimolar pyruvate and exogenous NAD-malate dehydrogenase and lactate dehydrogenase. The reaction, which did not occur in the absence of any one of these factors, was accompanied by the consumption of pyruvate; the ratio of O(2) evolved to pyruvate consumed was <0.5. When 0.1 millimolar [(14)C]malate was supplied most of the (14)C label was recovered as malate. At low concentrations of malate (<0.1 millimolar), the ratio of O(2) evolved to malate supplied was greater than 0.5. Chloroplasts catalyzed oxaloacetate-dependent O(2) evolution in approximate agreement with the theoretical stoichiometry for the light-coupled reduction of oxaloacetate to malate. Subsequent addition of NAD, pyruvate, NAD-malate dehydrogenase, and lactate dehydrogenase caused immediate resumption of O(2) evolution with the concomitant reduction of pyruvate to lactate externally to the chloroplasts. Resumption of O(2) evolution did not occur in the absence of oxaloacetate. The results are consistent with a mechanism in which oxaloacetate/malate cycles continuously between the chloroplasts and the external solution and serves as a carrier for the transfer of light-generated reducing equivalents for pyruvate reduction outside the chloroplast.